The mediating role of psychological capital between work stress and compassion fatigue among clinical nurses: a cross-sectional study - Chengxi Huang; Dengbin Liao; Yunting Luo; Yiran Xu; Haoyang Luo; Lingxiao He (Frontiers in Public Health, 2026)
Objective To explore the parallel multiple mediating effects of the sub-dimensions of psychological capital (self-efficacy, hope, resilience, and optimism) between work stress and compassion fatigue among clinical nurses. Methods A cross-sectional study was conducted using convenience sampling. Clinical nurses from a tertiary hospital were recruited. Data were collected using a general demographic questionnaire, the Nurse Work Stress Scale (NWSS), the Psychological Capital Questionnaire-revised (PCQ-R), and the Professional Quality of Life Scale (ProQOL). SPSS 29.0 was used for descriptive statistics and correlation analysis. The PROCESS macro (Model 4) was employed to test the parallel multiple mediation model. HC3 heteroscedasticity-consistent standard errors were used for significance testing of direct effects, and the bias-corrected bootstrap method (5,000 resamples) was applied to estimate the 95% confidence intervals (CI) for indirect effects. Sex, age, marital status, educational level, years of work experience, department, and night shifts per month were included as covariates. Results A total of 275 questionnaires were distributed and 274 were collected, yielding 273 valid responses (an effective response rate of 99.3%). The average age of the participating nurses was 32.74 ± 6.94 years. The score for work stress was 83.73 ± 24.15, psychological capital was 84.97 ± 19.53, and compassion fatigue was 58.55 ± 8.07. Pearson correlation analysis showed that work stress was significantly and positively correlated with compassion fatigue ( r = 0.537, P < 0.001), and psychological capital was significantly and negatively correlated with compassion fatigue ( r = −0.240, P < 0.01). The four sub-dimensions of psychological capital (self-efficacy, hope, resilience, and optimism) were also significantly and negatively correlated with compassion fatigue ( r = −0.137 ~-0.394, P < 0.05). After controlling for demographic and work-related covariates, the direct effect of work stress on compassion fatigue remained significant [ c' = 0.15, P < 0.001, 95% CI (0.10, 0.20)]. Among the four parallel mediators, only resilience showed a significant specific indirect effect [ effect = 0.058, 95% bootstrap CI (0.028, 0.091)]. The specific indirect effects through self-efficacy [ effect = −0.003, 95% CI (−0.024, 0.009)], hope [ effect = −0.007, 95% CI (−0.037, 0.028)], and optimism [ effect = −0.010, 95% CI (−0.033, 0.011)] were non-significant. Conclusion Among the four psychological capital dimensions, resilience demonstrated the strongest mediating association between work stress and compassion fatigue in this sample. Nursing managers should attach importance to the improvement of the working environment and implement targeted psychological resilience training interventions to reduce the incidence of compassion fatigue and stabilize the nursing workforce.